2006
DOI: 10.1159/000096192
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence Induces Stratum Corneum Vulnerability and Impairs the Skin Barrier Function in the Perianal Region

Abstract: Background: Incontinence leads to a reduced skin barrier function, while also increasing the risk of skin breakdown. Aim: To investigate the perianal skin barrier function of elderly patients with or without incontinence. Methods: We compared the skin barrier function by investigating the skin hydration, the skin pH, the amount of ceramide and by making a dermatological skin inspection of the perianal region in patients with and without incontinence. Results: Twenty-one incontinent patients (70.0%) showed a gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 56 publications
1
11
0
1
Order By: Relevance
“…Despite our understanding that the care of back and buttock skin is important for elderly nursing patients, and despite the fact that the itchiness and/or dryness of the skin occurs mainly on the trunk skin in the elderly, the SC functions of skin on the trunk have not been well investigated. Nakagami et al [4] compared the SC functions in perianal sites of elderly patients with or without incontinence, and found that the SC capacitance, skin pH and the amount of SC ceramide were greater in the incontinence group than in the healthy group. However, these results were obtained only from elderly patients, and therefore it is insufficient to understand the SC functions of skin on the trunk at different ages.…”
Section: Introductionmentioning
confidence: 99%
“…Despite our understanding that the care of back and buttock skin is important for elderly nursing patients, and despite the fact that the itchiness and/or dryness of the skin occurs mainly on the trunk skin in the elderly, the SC functions of skin on the trunk have not been well investigated. Nakagami et al [4] compared the SC functions in perianal sites of elderly patients with or without incontinence, and found that the SC capacitance, skin pH and the amount of SC ceramide were greater in the incontinence group than in the healthy group. However, these results were obtained only from elderly patients, and therefore it is insufficient to understand the SC functions of skin on the trunk at different ages.…”
Section: Introductionmentioning
confidence: 99%
“…6,5-7,5 dazu bei, dass der pH-Wert im Windelbereich auf 6,8-7,15 steigt [22]. Ein mittlerer Haut-pH-Wert von 7,15 wurde auch bei älteren Personen mit Inkontinenzvorlagen und Anzeichen von Hautschädigung festgestellt, verglichen mit einem pH-Wert von 6,35 auf ungeschädigter Haut und 6,03 bei Kontrollpersonen ohne Inkontinenz [26]. Der Anstieg des pH-Wertes ist unter anderem dadurch bedingt, dass Bakterien der Mikroflora, insbesondere Bacillus ammoniagenes , Harnstoff in Ammoniak umwandeln, und dass verschiedene Fäkalbakterien Ureasen produzieren.…”
Section: Windeldermatitis Und Inkontinenz-assoziierte Dermatitisunclassified
“…Noninvasive measures commonly used to evaluate skin maceration, including skin microscopy and measurements of TEWL, skin hydration, and skin pH [9][10][11][12], were applied to human skin. These measurements were not applied in the rat experiments because the measuring probes of these instruments were too large for the rat foot sole.…”
Section: Reproduction Of Skin Maceration In Humans and Ratsmentioning
confidence: 99%
“…The measurement of TEWL is widely used to evaluate skin barrier function, even in macerated skin [9,12]. However, we experienced difficulty accurately measuring TEWL in hydrated skin.…”
Section: Skin Barrier Function In Young Rat Skinmentioning
confidence: 99%
See 1 more Smart Citation